The Emerging Philippine Investment Environment - Myrna S. Austria (Philippine Institute for Development Studies (PIDS), 1998)
The change in the country's investment policies has been a crucial factor in building up confidence in the country's economic prospects. Despite the reforms undertaken, the country's performance in attracting foreign direct investment is still lower than its neighboring countries. This paper examines the factors that determine the foreign direct investment (FDI) and its behavior over time. It also analyzes the effectiveness of the Philippine incentive system particularly in the firms from the export processing and special economic zones.
Keywords: 330; investment opportunities; investment incentive system